On Partially Irregular Almost Periodic Solutions of Weakly Nonlinear Ordinary Differential Systems - Demenchuk, A. K. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
For weakly nonlinear almost periodic ordinary differential systems, we obtain conditions for the existence of partially irregular almost periodic solutions and propose algorithms for their construction.